1963
DOI: 10.1002/recl.19630821212
|View full text |Cite
|
Sign up to set email alerts
|

On Criegee's mechanism of ozonisation: The isolation of the six possible ozonides from methyl oleate

Abstract: Ozonisation of methyl oleate in.light petroleum at 10" yielded six ozonides. They were characterised as the three possible pairs of "cis-" and "trans-"isomers, which can be predicted on the basis of Criegee's theory. Our results indicate that a complete breakdown occurs of the oleate molecule into "zwitter-ionic" and aldehydic fragments. Hence we exclude a mechanism proposed by Milas, where a compbte breakdown of the molecule does not take place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1966
1966
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In 1963 the prediction of the Criegee mechanism relative to cross-ozonide formation was realized when two groups reported that ozonolysis of methyl oleate gave the three expected pairs (cis-trans) of ozonides. 43,44 Shortly thereafter a similar finding was reported for the simple olefin, pentene-2; that is, the ozonide cis-trans pairs from butene-2, pentene-2, and hexene-3 were all obtained.46 These results were obtained using the pure olefin as reactant and glpc to separate the products. The earlier failure of Criegee to obtain cross-ozonides in the case of heptene-3 could now probably be attributed to the olefin concentration used.…”
Section: Conversion Of the Initial Adduct Into Normal Ozonidementioning
confidence: 53%
“…In 1963 the prediction of the Criegee mechanism relative to cross-ozonide formation was realized when two groups reported that ozonolysis of methyl oleate gave the three expected pairs (cis-trans) of ozonides. 43,44 Shortly thereafter a similar finding was reported for the simple olefin, pentene-2; that is, the ozonide cis-trans pairs from butene-2, pentene-2, and hexene-3 were all obtained.46 These results were obtained using the pure olefin as reactant and glpc to separate the products. The earlier failure of Criegee to obtain cross-ozonides in the case of heptene-3 could now probably be attributed to the olefin concentration used.…”
Section: Conversion Of the Initial Adduct Into Normal Ozonidementioning
confidence: 53%
“…It includes: (1) interception of the zwitterion III by participating solvents to give substituted hydroperoxides II, or with reactive foreign aldehydes to give ozonides other than that of the olefin itself;4 (2) the formation of the same ozonide from two structurally different olefins which, however, yield the same zwitterion and carbonyl moieties;4 (3) the formation of cyclic oxyhydroperoxides from olefins having a properly placed hydroxy functional group;5 and (4) the formation of cross ozonides6 *from unsymmetrical olefins. [7][8][9][10][11]…”
Section: Methodsmentioning
confidence: 99%
“…Many studies on the ozonolysis of organic compounds have been conducted involving low-molecular-weight olefins [12][13][14][15]. The products of ozonolysis contain the molecular segment of 1,2,4-trioxolane, which readily degrades into acyclic carbonyl compounds [15][16][17][18] Few studies focused on the ozonolysis of long-chain fatty acids and their alkenyl esters.…”
Section: Oleic Acid and Its Esters As Components Of The [3+2] Cycload...mentioning
confidence: 99%